A Financial Feasibility Analysis and Supply Chain of XYZ Rice Polishing Business - Agus Priyanto; Titik Ekowati; Komalawati Komalawati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The increasing demand for premium rice in Indonesia has opened up opportunities for rice polishing businesses to increase added value and competitiveness. Challenges such as rising raw material prices, increased operational costs, and process efficiency have become obstacles in maintaining the sustainability and competitiveness of these businesses. This study aims to analyze the financial feasibility and supply chain structure of the rice polishing business at UD XYZ, ABC Regency, South Sulawesi. A case study method was used with a quantitative and qualitative descriptive approach. The financial analysis included NPV, IRR, B/C ratio, PI, ROI, payback period, and sensitivity analysis. The supply chain structure is analyzed through product, financial, and information flow mapping. The results show that UD XYZ is a small-scale business and is financially feasible to operate with a positive NPV, IRR higher than the benchmark interest rate, B/C and PI greater than 1, profitable ROI, and good financial indicators, although it is vulnerable to variable cost increases of more than 2%. The supply chain is relatively short, from rice milling to end consumers. These findings have important implications for business actors and policymakers in the development of the rice polishing industry in production centers.